A redemocratização brasileira e a questão da memória: da Lei de anistia ao governo Bolsonaro - Teixeira, Dayana Alves (2022)
The objective of this work is to analyze the Brazilian redemocratization process understanding it’s path since the 1979 Amnesty Law up to Bolsonaro’s government. It is understood that the rise and strengthening of Bolsonarism in the country affects the social memory built around the civil-military dictatorship period of 1964-1985. With a descriptive and qualitative research, it uses books, articles, documentaries and reports to analyze the reparation measures applied by the Transitional Justice and its impacts. Thus, it is clear that the instability of Brazilian democracy has roots in its redemocratization process based on forgetfulness and impunity, which today corroborates the democratic crisis that takes place with the very instruments of democracy.